What are the Employee Performance Model Determinants in Indonesia Manufacturing Industry? - Ikramina Larasati Hazrati Havidz; Bagas Pria Nugraha (Universitas Batanghari Jambi, 2023)
Boss-subordinate (guanxi) relations in the organization are important in encouraging and increasing productivity. The involvement of these relationships in the company creates a good improvement and development of workers. Motivation and job satisfaction are things that influenced by good guanxi relations. This study aims to identify employee performance from superior-subordinate relationships (guanxi) on motivation, worker satisfaction with the moderation effect of Islamic work ethic. This study used purposive sampling as a method involving 210 workers from office employees in a multinational manufacturing industry in Indonesia. Data is tested with SEM (Structural Equation Model) as the method and data analysis using Smart PLS 3 (Partial Least Square) as the software. The study shows superior-subordinates (guanxi) have a significant direct and positive effect on motivation and job satisfaction. Furthermore, motivation and job satisfaction have a significant direct positive effect on employee performance. While the moderation effect of Islamic work ethic has no impact or has no influence on motivation to job satisfaction. improving superior-subordinate relations (guanxi) in the company, may impact the motivation, job satisfaction, and employee performance.